Reflections XIX and XX: Reflections from Education and the Arts in the COVID-19 Era - Desai, Dipti; Solomon, Naisha B.; Charnley, Amanda (Communiars. Revista de Imagen, Artes y Educación Crítica y Social, 2020)
Dipti Desai developed Reflection XIX. Desai is a Professor of Art and Art Education and she is a reference in the field of art education in activist contexts. She is also Director of Art +Education Programs, Department of Art and Art Professions, Steinhardt School of Culture, Education and Human Development, New York University. Reflection XX is developed by Naisha B. Solomon and Amanda Charnley, graduate students in the Art, Education, and Community Practice program in the Department of Art and Art Professions, Steinhardt School of Culture, Education and Human Development, New York University.